La fractalidad de la educación virtual: naturaleza y estructura - Turpo Gebera, Osbaldo (Pontificia Universidad Católica del Perú. Fondo Editorial, 2013)
The potential generated by ICT in education raises reflect on the underlying frameworks. In this sense, the fractal is an opportunity to explain how it organizes and manages virtual education.This approach recognizes that educational dynamics are recursive and iterative processes instituted as progressive sequences, by way of fractals. This understanding enables becoming as mediated and articulated successive levels. In each dimension are embodied own activities and in turn, involves the recurrence of subsequent levels as possible solving of problem situations. Thus, the knowledge built in response to a collaborative action, participation in networks, ranging from autonomous to the cultural level or conversely.

La aplicación de las TIC en la educación suscita reflexionar sobre los marcos estructurales que la fundamentan. En ese sentido, la fractalidad constituye una aproximación a cómo se organiza y gestiona la educación virtual.Este abordaje reconoce que en la dinámica educativa existen procesos recursivos e iterativos instituidos como secuencias progresivas, a modo de los fractales. Su devenir posibilita su comprensión como un sistema mediado por niveles sucesivos y articulados. En cada dimensión se plasman actividades propias, y a su vez, involucra la recurrencia a los subsiguientes niveles, como posibilidad resolutiva de las situaciones problemáticas. Así, el conocimiento construido responde a una acción colaborativa, de participación en red, desde el nivel autónomo hasta el cultural o viceversa.
The virtual education fractality: nature and organization
Keywords: Virtualidad; Fractalidad; Educación Virtual; Interactividad; Factores Educativos; Virtuality; Fractality; Virtual Education; Interactivity; Educational Factors; https://purl.org/pe-repo/ocde/ford#5.03.00